Resolving hyperelasticity-adhesiveness conflict in polymer networks by in situ constructing mechanical heterogeneities - Ping Zhang; Haowei Ruan; Qingxian Li; Yunfeng He; Canhui Yang (Nature Communications)
Abstract Stretchable materials with low hysteresis and strong adhesion are needed in applications, but unifying the two contradictory mechanical properties is challenging. Herein, we propose the design principles of polymer networks that are hyperelastic yet adhesive by rationalizing mechanical heterogeneities. The heterogeneous networks comprise a viscoelastic adhesive surface and a hyperelastic non-adhesive bulk. The former has a stiffness much smaller than that of the latter. We synthesize the networks by harnessing the oxygen inhibition mechanism, construct a polymerization phase diagram by reconciling the kinetics of polymerization and radical quenching of oxygen, and establish a power law criterion for the transition from a viscoelastic adhesive network to a hyperelastic adhesive network. We illustrate the principle with heterogeneous poly(butyl acrylate-co-acrylic acid) networks, achieving hysteresis <5% and adhesion energy >300 J/m2. We show that the adhesion energy-thickness relation of hyperelastic adhesive polymer networks is nonlinear below a transition thickness. Hyperelastic and adhesive stretchable materials potentialize high-cycle and fatigue-resistant soft human-machine interfaces and beyond.